1990
DOI: 10.1161/01.cir.81.1.137
|View full text |Cite
|
Sign up to set email alerts
|

Trends in congenital heart disease in Dallas County births. 1971-1984.

Abstract: To examine the changes in birth cohort prevalence rates and severity of congenital heart disease, we studied children with congenital heart disease born to blacks, whites, and Mexican-Americans in Dallas County from 1971 through 1984. Diagnoses were made by pediatric cardiologists' clinical evaluations, echocardiography, catheterization, surgery, or autopsy. During this study period, 2,509 of 379,561 liveborn infants were diagnosed, a prevalence rate of 6.6/1000. The rates for whites was significantly higher t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
56
1
4

Year Published

1992
1992
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(70 citation statements)
references
References 6 publications
9
56
1
4
Order By: Relevance
“…Investigators in North America and elsewhere noted an increase in specific heart defects, including pulmonic stenosis and ventricular, atrial, and atrioventricular septal defects, [7][8][9]19,20 during the 1970s and 1980s. [7][8][9]11,19,[21][22][23] Our findings document a continuation of such trends well into the 1990s.…”
Section: Discussionmentioning
confidence: 99%
“…Investigators in North America and elsewhere noted an increase in specific heart defects, including pulmonic stenosis and ventricular, atrial, and atrioventricular septal defects, [7][8][9]19,20 during the 1970s and 1980s. [7][8][9]11,19,[21][22][23] Our findings document a continuation of such trends well into the 1990s.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] [ Table 2] shows the prevalence of CHDs in India. [7][8][9][25][26][27][28][29][30] Studies in Chandigarh showed the maximum prevalence of 50.89 per 1000 live births [9] whereas studies in Shimla showed the minimum of 2.25 per 1000 live births.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, the rapid development of the world may increase many risk factors to develop CHD such as pollutants and teratogens. The number of births with CHD in Dallas county suggests an apparent increase in prevalence from approximately 5% in 1971 to 8% in 1984 (Fixler et al, 1990). Within the Baltimore-Washington Infant Study Group, the prevalence of CHD increased from 2.8 per 1,000 live births in 1981 to 4.3 per 1,000 live births in 1988 (Ferencz et al, 1989) and a recent report from North England demonstrated the total prevalence of CHD increased from 5.4 per 1,000 births and terminations of pregnancy in 1985 to 11.6 per 1,000 births and terminations of pregnancy in (Dadvand et al, 2008.…”
Section: Birth Prevalencementioning
confidence: 99%